PENGARUH SUPERVISI KEPALA RUANG MODEL REFLEKTIF TERHADAP KEPUASAN KERJA PERAWAT DI RSUD TUGUREJO PROVINSI JAWA TENGAH - Fatikhah Fatikhah; Nur zuhri (Jurnal Surya Muda, 2019)
Nurses’ job satisfactioninfluences the quality of nursing services. The improperly managed job satisfaction of nurses can disrupt the function of the hospital in providing comprehensive and quality health services. The nurses’ job satisfaction can be achieved through a good relationship between nurses and hospital leaders. A good and equal as well as supporting and collaborative relationshipis reflected in the supervision of reflective model. This study aimed to analyze the influence of head nurses’ supervision of reflective model on the job satisfaction of nursesat Tugurejo Regional Public Hospital in Central Java Province. This study employed a pre-post-test quasi-experimental design with a control group. The samples were 68 nurses recruited by purposive sampling and were assigned to the intervention group (n = 34) and control group (n = 34). The data were collected using questionnaires and then analyzed using the paired t-test. The result of paired t-test test obtained a p-value of < 0.001, indicating that there were influences of the head nurses’ supervision of reflective model on the nurses’ job satisfaction. The reflectivemodel supervision can be used as an alternative to improve the job satisfaction among the nurses. The head nurses as a low-level manager can perform the management functions well through the reflective model supervision to improve the nurses’ job satisfaction.